Anti-PD-1 therapy in patients with advanced melanoma and preexisting autoimmune disorders or major toxicity with ipilimumab - Menzies, Alexander; Hassel, Jessica C. (Annals of oncology, 2017)
Background. Anti-PD-1 antibodies (anti-PD-1) have clinical activity in a number of malignancies. All clinical trials have excluded patients with significant pr
Published: 29 September 2016
Gesehen am 26.09.2018